Strategies of Islamic Religious Education Teachers in Addressing Bullying Behavior Among Students - Slamet Ahyarul Umam; Ridho Riyanto (Manunggal Halim Jaya, 2026)
Bullying is a negative behavior that frequently occurs in school environments and affects students’ psychological, social, and academic development. In faith-based schools such as MIM Kebondalem, the internalization of Islamic values is expected to prevent such behavior. This study aims to analyze the strategies of Islamic Religious Education (PAI) teachers in addressing bullying. The research employs a qualitative method with a case study approach. Data sources include the principal, PAI teachers, students, and parents, with data collected through interviews, observations, and documentation. The analysis is conducted descriptively through data reduction, data display, and verification. The findings reveal that PAI teachers implement holistic strategies grounded in religious values, such as habituating noble character, providing exemplary behavior, offering moral advice, and applying educational sanctions in preventive, curative, and persuasive ways. These strategies are supported by school programs and parental involvement. In conclusion, these strategies are effective in shaping Islamic character and can serve as a model for addressing bullying in faith-based schools.